The Motion of Surface with Constant Negative Gaussian Curvature (Journal of Partial Differential Equations, 1999)
In this paper, an approach is suggested to consider the relation between the integrable equation and the motion of surface with constant negative Gaussian curvature.
Keywords: Integrable equations; motion of surface; surface with constant negative Gaussian curvature